Healthcare coverage and disability evaluation for reserve component personnel : research for the 11th Quadrennial Review of Military Compensation - Hosek, Susan D. (Rand Corporation monograph series, 2012)
Because Reserve Component (RC) members have been increasingly used in an operational capacity, among the policy issues being addressed by the 11th Quadrennial Review of Military Compensation (QRMC) is compensation and benefits for the National Guard and Reserve. As part of the review, RAND was asked to analyze healthcare coverage and disability benefits for RC members, including participation in the TRICARE Reserve Select (TRS) program, the potential effects of national health reform on coverage rates, and disability evaluation outcomes for RC members. This report summarizes the results of RAND's analysis. The author finds that 30 percent of RC members lack health insurance to cover care for non-service-related conditions. The TRS program offers the option of purchasing health insurance through the military on terms that are superior to typical employer benefits. Although program participation has increased, it remains low and TRS does not appear to be effectively targeting those most likely to be uninsured. TRS premiums are also lower than the premiums for the new options that will be available under health reform and the same as the penalty for not being insured. So health reform is likely to increase TRS enrollment. Finally, previously deployed RC members are referred to the Disability Evaluation System at a much lower rate than Active Component (AC) members, even for deployment-related conditions, but those who are referred receive dispositions (and thus benefits) similar to those for AC members. These findings suggest that the Department of Defense may want to consider ways to better coordinate TRS with other insurance options that will be available to RC members and that the identification of RC members who experience health consequences from deployment leading to disability merits further investigation.